Micromolar sodium fluoride promotes osteo/odontogenic differentiation in dental pulp stem cells by inhibiting PI3K/AKT pathway - Xu, Shuaimei; Xie, Xinghuan; Li, Changzhou; Liu, Zhongjun; Zuo, Daming (Archives of oral biology, 2021)
Sodium fluoride (NaF) plays an important role in preventing dental caries. However, the regulatory effect of NaF on the committed differentiation of DPSCs is not fully understood. In this study, we characterized the impact of micromolar levels of NaF on the osteo/odontogenic differentiation of DPSCs. DPSCs were isolated from healthy human third molars and were cultured in conditioned media with different concentrations of NaF. RNA sequencing (RNA-seq) combined with Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis was used to assess the pathways regulated by NaF. Alkaline phosphatase activity, Alizarin red staining, Western blotting, and real-time qRT-PCR were used to determine the osteo/odontogenic differentiation in DPSCs treated with NaF. NaF significantly promoted the osteo/odontogenic differentiation of DPSCs at micromolar levels. Furthermore, RNA-seq and KEGG pathway enrichment analysis indicated that the PI3K/AKT pathway was involved in the pro-osteoclastogenesis effect of NaF. Western blotting analysis exhibited that the phosphorylation of AKT was decreased in NaF-treated DPSCs. Chemical inhibition of the PI3K/AKT pathway abrogated the NaF-promoted DPSCs osteo/odontogenic differentiation. Micromolar NaF can promote the osteo/odontogenic differentiation of DPSCs by inhibiting the PI3K/AKT pathway. The data used to support the findings of this study are available from the corresponding author upon request. •Micromolar NaF promotes osteo/odontogenic differentiation of DPSCs.•Activation of PI3K/AKT pathway is suppressed in NaF-treated DPSCs.•NaF affects DPSC differentiation via the PI3K/AKT pathway.